Chemical Composition and Health Risk Assessment of Rainwater Around a Cement Factory in Ibeshe, Ogun state - Oguntade, Bukunola Kehinde; Hunge, Comfort Pelumi; Onwordi, Chionyendua Theresa; Adegboyo, Opeyemi Olayinka (European Journal of Applied Sciences, 2024)
Rainwater harvesting has become a common source of water for many households in developing countries. An analysis of the anions and cations of rooftop harvested rainwater near a cement production factory in Yewa South, Ogun State, Nigeria was evaluated. The bulk samples were collected from April-September 2022 at weekly intervals. Parameters determined in the samples were pH, temperature, chloride, flouride, NOx, and cations such as sodium, calcium, potassium, magnesium, Aluminium, lead, and silicon. Results of the analysis showed that the rainwater was basic at all the sample locations, while all other variables (except Al3+, Pb2+, Si4+, and Cl-) were within the World Health Organization (WHO) drinking water standard. It also revealed that the presence of the cement factory does not have a huge impact on the characteristics of the rainwater in the study area, However, periodical monitoring of rainwater composition is important as the result obtained for this study may likely change with time.